2014
DOI: 10.1542/peds.2012-3356
|View full text |Cite
|
Sign up to set email alerts
|

Residual Scarring From Hidradenitis Suppurativa: Fractionated CO2 Laser as a Novel and Noninvasive Approach

Abstract: Hidradenitis suppurativa (HS) is a chronic, relapsing, inflammatory skin condition that can have a significant psychosocial impact, both with the active disease and with residual scarring. Although a wide variety of treatment options exist for HS, to our knowledge there are no reported modalities aimed specifically at treating HS scarring. We describe the case of an adolescent female who received medical management of intramammary HS followed by successful treatment with fractionated 10 600-nm carbon dioxide l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Pediatric cases of HS are rare and often demonstrate endocrine aberrancy. Hidradenitis suppurativa has been reported in an infant with congenital adrenal hyperplasia, an obese girl younger than 8 after premature adrenarche, an obese prepubertal 8‐year‐old girl, and a 15‐year‐old girl with polycystic ovary syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric cases of HS are rare and often demonstrate endocrine aberrancy. Hidradenitis suppurativa has been reported in an infant with congenital adrenal hyperplasia, an obese girl younger than 8 after premature adrenarche, an obese prepubertal 8‐year‐old girl, and a 15‐year‐old girl with polycystic ovary syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Krakowski et al 10 reported a case of a pediatric patient whose HS was controlled with medical management. However, she experienced psychological distress over the appearance of cribriform scarring in the inframammary region.…”
Section: Discussionmentioning
confidence: 99%
“…The scarring was treated with 2 sessions of fractional CO 2 laser separated by 2 months, which resulted in reduced erythema, improved texture, pliability, and appearance of the scar. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Efficacy for AFR has been reported in a variety of dermatologic conditions in the pediatric population including scars related to hidradenitis suppurativa and burn scar‐related nail dystrophy, palliative treatment of lymphangioma circumscriptum, and for the fibro‐ fatty residua seen after involution of infantile hemangiomas . AFR employs high energy, short duration pulses from a 2,940‐nm or 10,600‐nm laser to vaporize tissue in a pixelated pattern at a depth and density determined by the operator .…”
Section: Discussionmentioning
confidence: 99%